Spirometry in healthy men: a correlation with smoking and with mild symptoms. Issue 3 (June 1978) - Prieto, F; English, M J; Cochrane, G M; Clark, T J; Rigden, B G
Abstract : Symptoms, smoking history, and variates taken from the forced expiratory manoeuvre were studied in a group of 271 healthy men attending a mass radiography unit. It was found that correlation of the forced expiratory ratio (FEV1/FVC) with the presence of mild or moderate respiratory symptoms was at least as satisfactory as that of technically more complicated measurements such as MEF50 and MEF75. In asymptomatic individuals those differences associated with smoking were the same for FEV1/FVC as for MEF75. Asymptomatic abnormalities of lung function were not observed. Simple measurements such as FEV1/FVC can therefore provide as much information from a forced expiratory manoeuvre to screen for early airways obstruction as MEF50 and MEF75.